Affective Contagion: How Attitudes Expressed by Others Influence Our Perception of Actions - Di Cesare, Giuseppe; Pelosi, Annalisa; Aresta, Silvia Maria; Lombardi, Giada; Sciutti, Alessandra (Frontiers in Human Neuroscience, 2021)
Vitality forms represent a fundamental aspect of social interactions by characterizing how actions are performed and how words are pronounced on the basis of the attitude of the agent. Same action, such as a handshake, may have a different impact on the receiver when it is performed kindly or vigorously, and similarly, a gentle or rude tone of voice may have a different impact on the listener. In the present study, we carried out two experiments that aimed to investigate whether and how vocal requests conveying different vitality forms can influence the perception of goal-directed actions and to measure the duration of this effect over time. More specifically, participants were asked to listen to the voice of an actor pronouncing “give me” in a rude or gentle way. Then, they were asked to observe the initial part of a rude or a gentle passing action, continue it mentally, and estimate the time of its completion. Results showed that the perception of different vitality forms expressed by vocal requests influenced the estimation of action duration. Moreover, we found that this effect was limited to a certain time interval (800 ms), after which it started to decay.